ANALISIS PENYEDIAAN RUMAH KHUSUS UNTUK NELAYAN DAN TINGKAT KEPUASAN PENGGUNA TERHADAP FASILITAS YANG TERSEDIA - Miranie Trie Amanda; Fepy Supriyani; Annisa Fitria Edriani (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2022)
Provision of special houses for fishermen continues from year to year as a part of the government's efforts to transform coastal areas into well-ordered and habitable residential areas. Inappropriate targeting and user satisfaction levels that may differ from the government in the available facilities are a problem in providing special houses for fishermen. The purpose of this research was to determined the utilization in the provision of special houses was right on target for the fishing community and to determine the level of user satisfaction with the available facilities. The research method was carried out by distributing questionnaires to respondents for special housing for fishermen in Tanggo Raso Village, Pino Raya District, South Bengkulu Regency. The data from the questionnaire results were processed and analyzed using the SPSS 25 program which included validity testing, reliability testing, and multiple linear regression analysis with a 90% confidence level. The results showed that the special house users were right on target for the fishing community and the level of user satisfaction which was influenced by facilities and infrastructure, location factors, and building physical condition factors was 60.4%. The most dominant factor affected the level of user satisfaction was the location factor of 31.1%. The facility and infrastructure factor was 18.5% and the building physical condition factor was 10.8%.